Evaluating an educational intervention to improve the accuracy of death certification among trainees from various specialties - Villar Jesús; Pérez-Méndez Lina (BMC, 2007)
Abstract Background The inaccuracy of death certification can lead to the misallocation of resources in health care programs and research. We evaluated the rate of errors in the completion of death certificates among medical residents from various specialties, before and after an educational intervention which was designed to improve the accuracy in the certification of the cause of death. Methods A 90-min seminar was delivered to seven mixed groups of medical trainees (n = 166) from several health care institutions in Spain. Physicians were asked to read and anonymously complete a same case-scenario of death certification before and after the seminar. We compared the rates of errors and the impact of the educational intervention before and after the seminar. Results A total of 332 death certificates (166 completed before and 166 completed after the intervention) were audited. Death certificates were completed with errors by 71.1% of the physicians before the educational intervention. Following the seminar, the proportion of death certificates with errors decreased to 9% (p < 0.0001). The most common error in the completion of death certificates was the listing of the mechanism of death instead of the cause of death. Before the seminar, 56.8% listed respiratory or cardiac arrest as the immediate cause of death. None of the participants listed any mechanism of death after the educational intervention (p < 0.0001). Conclusion Major errors in the completion of the correct cause of death on death certificates are common among medical residents. A simple educational intervention can dramatically improve the accuracy in the completion of death certificates by physicians.